The Observation of Meiotic Union Behavior of Gametophytes Provides a New Basis for Ploidy of Carassius auratus gibelio - Kexin Ma; Yueyao Yang; Yifan Li; Chuan Li; Taicheng Li; Haiyan Ma; Zibin Jiang; He Zhou; Wei Wang (Animals)
As an important aquaculture fish, the genus Carassius exhibits different ploidy, including tetraploids and hexaploids [...]